Analogs of the Frog-skin Antimicrobial Peptide Temporin 1Tb Exhibit a Wider Spectrum of Activity and a Stronger Antibiofilm Potential as Compared to the Parental Peptide - Grassi, Lucia; Maisetta, Giuseppantonio; Maccari, Giuseppe; Esin, Semih; Batoni, Giovanna (Frontiers in Chemistry, 2017)
The frog skin-derived peptide Temporin 1Tb (TB) has gained increasing attention as novel antimicrobial agent for the treatment of antibiotic-resistant and/or biofilm-mediated infections. Nevertheless, such a peptide possesses a preferential spectrum of action against Gram-positive bacteria. In order to improve the therapeutic potential of TB, the present study evaluated the antibacterial and antibiofilm activities of two TB analogues against medically relevant bacterial species. Of the two analogues, TB_KKG6A has been previously described in the literature, while TB_L1FK is a new analogue designed by us through statistical-based computational strategies. Both TB analogues displayed a faster and stronger bactericidal activity than the parental peptide, especially against Gram-negative bacteria in planktonic form. Differently from the parental peptide, TB_KKG6A and TB_L1FK were able to inhibit the formation of Staphylococcus aureus biofilms by more than 50% at 12 μM, while only TB_KKG6A prevented the formation of Pseudomonas aeruginosa biofilms at 24 μM. A marked antibiofilm activity against preformed biofilms of both bacterial species was observed for the two TB analogues when used in combination with EDTA. Analysis of synergism at the cellular level suggested that the antibiofilm activity exerted by the peptide-EDTA combinations against mature biofilms might be due mainly to a disaggregating effect on the extracellular matrix in the case of S. aureus, and to a direct activity on biofilm-embedded cells in the case of P. aeruginosa. Both analogues displayed a low hemolytic effect at the active concentrations and, overall, TB_L1FK resulted less cytotoxic towards mammalian cells. Collectively, the results obtained demonstrated that subtle changes in the primary sequence of TB may provide TB analogues that, used alone or in combination with adjuvant molecules such as EDTA, exhibit promising features against both planktonic and biofilm cells of medically relevant bacteria.